Synthesis and characterization of agricultural waste carbon-based structures for application in sensing - Magagula, Lindokuhle Precious (My University, 2022)
Rapid population and economic growths, excessive use of fossil fuels, and climate change have contributed to a serious turn towards environmental management and sustainability. The agricultural sector is a big contributor to (lignocellulosic) waste, which accumulates in landfills and ultimately gets burnt, polluting the environment. In response to the current climate change crisis, policy makers and researchers are respectively encouraging and seeking ways of creating value-added products from generated waste. Recently, agricultural waste is making a regular appearance in articles communicating about the production of a range of carbon and polymeric materials worldwide, this has led to a promising concept of waste to wealth in the modern world. The use of biomass waste such as corncob (CC) for the extraction of cellulose nanocrystals (CNCs), synthesis of carbon quantum dots (CQDs), and preparation of activated carbon (AC), has recently gained interest in the area of waste recycling and management. Further, the new materials generated from this waste promise to be effective and competitive in emerging markets. In this study, CC waste was used as a feedstock for preparation of CNCs, CQDs, and AC (shown in figure 1), for sensing applications. CNCs extracted from CC using acid hydrolysis were compared to the CNCs prepared from commercial microcrystalline cellulose (MCC). The CNCs from CC and MCC revealed comparable thermal, surface/structural, and crystallinity. These were confirmed by various characterization techniques including scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), thermogravimetric Analysis (TGA), and Fourier transform infrared (FT-IR). For further comparison on the effect of the hydrolysis, nitro -oxidation was used to prepare nitro-oxidized cellulose nanocrystals (NOCNCs) from CC. The crystallinity indexes of the NOCNCs was obtained to be 74.37 %, which was significantly higher than that of MCC-CNCs (70.24 %), and CC-CNCs (69.12 %). TEM analysis confirmed that the CNCs had different morphologies, while SEM was used to determine the morphological properties of the samples prior to acid hydrolysis. The as-prepared CC-CNCs and MCC-CNCs were then utilized to prepare highly luminescent nitrogen doped carbon materials, with a high degree of functional groups, sensitivity, and selectivity towards Fe3+ . CQDs showed great potential for fluorescent sensor applications. Incorporation of surface functional groups such as nitrogen and oxygen containing groups were confirmed by FT-IR and X-ray photoelectron spectroscopy (XPS) analysis which showed that the prepared N-CQDs were highly functionalized with these heteroatoms, resulting in an excitation-dependent fluorescence emission. The iii detection limit of Fe3+ was obtained to be 70 nM and 75 nM, for the CC-CNCs and MCC-CNCs derived fluorescent carbon materials, respectively. Due to its natural porous nature, the corncob was also utilized to prepare activated carbons by chemical activation with potassium carbonate (activating agent) at 800 °C using varied ratios of impregnation. Highly porous corncob derived activated carbon (ACC) material with a surface area of 1523.2 m2 /g and a pore volume = 0.81 cm3 /g was. The as-prepared ACC was then decorated with various percentage loadings copper oxide nanoparticles (CuO NPs) was achieved, which produced composites with surface areas and porosity. Simple and room temperature operable sensors based on ACC and the composites were designed on gold-plated interdigitated electrodes (IDEs) embedded on a printed-circuit board (PCB) substrate. The results showed that CuO NPs play an important role in enhancing sensor performance of the ACC since its incorporation improved on the conductivity and response when compared to the ACC-based sensor. The ACC/PVA/CuO 15% sensor demonstrated good reproducibility of the sensing signal when exposed to 100 ppm ethanol vapors for up to four cycles. The sensor exhibited a response and recovery of 125 and 130 seconds, respectively, when exposed to 100 ppm of ethanol. Hence, the ACC/CuO composites could be a future candidate for ethanol gas sensing application at room temperature.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Agricultural Waste Carbon-based Structures; Environmental management and sustainability